Analyses using genomic and transcriptomic data of mads-box genes in Elaeis guineensis - Suhaila Sulaiman,; Lee, Yang Ping; Kwan, Yen Yen; Sharifah Shahrul Rabiah Syed Alwee, (Penerbit Universiti Kebangsaan Malaysia, 2017)
MADS-box genes encode a group of transcription factor family, well known as key regulators of plant vegetative and development processes, including flowering. Here, we aimed at analysing MADS-box genes in African oil palm (Elaeis guineensis) genome, the pre-dominant source of worldwide production of vegetable oils. A total of 209 potential MADSbox genes are identified in the published 1.8 Gb E. guineensis draft genome. A de novo assembly of RNA-seq data from inflorescence tissues was constructed using Trinity software. The analysed transcriptome data has validated 36 full-length genes, inclusive of seven transcripts that were previously annotated to encode unknown proteins. Of the 36 genes discovered, 21 genes were characterised as Type I MADS-box genes and phylogenetic analysis using maximum likelihood approach further classified them into three sub-groups of Mα, Mβ and Mγ. Based on in silico analyses, we have successfully identified one gene annotated as unknown protein to contain a domain of “MADS-box transcription factor”. Its differential expression data, comparison between normal and mantled inflorescence of oil palm, suggested the involvement of the gene in the mantling related process. The findings contribute to updated oil palm genome information which may potentially lead to future understanding of the association of MADS-box genes in mantled oil palm. This may also lead to a resource for biomarker discovery.